A new manner of reporting pressure results after glaucoma surgery - Bordeianu CD (Dove Medical Press, 2011)
Constantin-Dan Bordeianu1, Cristina-Eugenia Ticu21Department of Ophthalmology, Emergency Hospital, Ploiesti, Romania; 2Provisional Candidate for PhD, Edmonton, AB, CanadaPurpose: To evaluate to what extent contemporary glaucoma abstracts offer complete information and to suggest a new manner of pressure results reporting.Materials, methods, and results: Most of the 36 relevant surgical glaucoma abstracts found in one issue of International Glaucoma Review contain insufficient data-supported statements. Such abstracts cannot offer a clear picture of the study essence if economic, linguistic, or political barriers prevent access to the full text. In order to enrich abstract content and to avoid typographic space waste, a formula is suggested to provide, in one single line of symbols and figures, all the necessary data for statistical interpretation at two evolution moments: the first significative control (6 months) and the final one.Conclusion: The current manner of results reporting in surgical glaucoma abstracts is subject to too little standardization, allowing insufficiently data-supported statements. Abstracts, especially those printed in small-circulation language journals, should be conceived and standardized in such a manner that any abstract review reader is capable of grasping the essence of the study at first glance. The suggested manner of reporting results would bring satisfaction to all areas of the process. Publishers would save typographic space, readers would find all the necessary data for statistical analysis and comparison with other studies, and authors would be convinced that the essence of their work would penetrate in spite of any economic, linguistic, or political barriers.Keywords: glaucoma, reporting results, IOP, abstract construction, standardization formula